Influence of Chemical Components of Oil Palm on Properties of Binderless Particleboard - Junidah, Lamaming; Othman, Sulaiman; Tomoko, Sugimoto; Rokiah, Hashim; Norafizah, Said; Masatoshi, Sato (NC State University, 2013)
The influence of chemical components of oil palm on properties of binderless particleboard were evaluated through a series of mechanical, physical, and chemical analyses in order to assess the self-bonding mechanism. Binderless particleboards were evaluated by relating the physical and mechanical properties to the chemical components. Results revealed that the addition of glucose and sucrose onto the board with and without extraction increased the modulus of rupture and internal bond strength. Glucose and sucrose also reduced the thickness swelling and water absorption of the board. The addition of starch onto the board enhanced the strength of the board, though sugar addition enhanced the board strength more than starch. Adding the sugar also lowered the xylose/ arabinose ratio, indicating that the boards consist of short-chain polymers with a large amount of branching with other monosaccharides. This implies that sugar content present in oil palm trunk plays a major role in the bonding of binderless boards.